THE MAIN ROLE OF INTONATION IN PRAGMATICS - Majidova Maftuna Murod qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
In this article demonstrates the importances of intonation in pragmatics. Also, what kind of accents have according to American English. At the same time in this article clarify the types of intonation with the clear examples.